2023
DOI: 10.3390/ijms24098031
|View full text |Cite
|
Sign up to set email alerts
|

Uremic Toxin Indoxyl Sulfate Promotes Macrophage-Associated Low-Grade Inflammation and Epithelial Cell Senescence

Abstract: In this study, we investigated the impact of the uremic toxin indoxyl sulfate on macrophages and tubular epithelial cells and its role in modulating the response to lipopolysaccharide (LPS). Indoxyl sulfate accumulates in the blood of patients with chronic kidney disease (CKD) and is a predictor of overall and cardiovascular morbidity/mortality. To simulate the uremic condition, primary macrophages and tubular epithelial cells were incubated with indoxyl sulfate at low concentrations as well as concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Elevated IS levels induce oxidative stress and inflammation in renal tubular cells, promoting fibrosis and accelerating the decline in renal function ( Barreto et al, 2009 ). Moreover, IS was also found to be increased in MASLD patients ( Hotamisligil, 2006 ; Ribeiro et al, 2023 ). Mechanistically, IS activates the aryl hydrocarbon receptor (AhR) pathway and induces the expression of TGF-β and pro-inflammatory cytokines, thereby exacerbating renal injury ( Delgado-Marin et al, 2024 ).…”
Section: Renal Complications In Masld/mashmentioning
confidence: 87%
“…Elevated IS levels induce oxidative stress and inflammation in renal tubular cells, promoting fibrosis and accelerating the decline in renal function ( Barreto et al, 2009 ). Moreover, IS was also found to be increased in MASLD patients ( Hotamisligil, 2006 ; Ribeiro et al, 2023 ). Mechanistically, IS activates the aryl hydrocarbon receptor (AhR) pathway and induces the expression of TGF-β and pro-inflammatory cytokines, thereby exacerbating renal injury ( Delgado-Marin et al, 2024 ).…”
Section: Renal Complications In Masld/mashmentioning
confidence: 87%
“…Accumulation of toxins and proinflammatory cytokines may constitute DAMPs to which endothelial cells are continuously exposed. In parallel, the increase in toxic substances provokes immunodeficiency in CKD patients, leading to a suppression of humoral and immune responses [76]. Multiple studies demonstrated that the accumulation of GDUTs leads to the occurrence and development of CKD and increases the risk of cardiovascular events in CKD [24,[77][78][79][80].…”
Section: Uremic Toxins (Uts) and Gut-derived Uremic Toxins (Gduts) In...mentioning
confidence: 99%